2020
DOI: 10.1186/s41100-020-00286-9
|View full text |Cite
|
Sign up to set email alerts
|

Annual dialysis data report for 2018, JSDT Renal Data Registry: survey methods, facility data, incidence, prevalence, and mortality

Abstract: The annual survey of the Japanese Society for Dialysis Therapy Renal Data Registry (JRDR) was sent to 4458 dialysis facilities at the end of 2018; among these facilities, 4402 facilities (98.7%) responded to the facility questionnaire, and 4222 (94.7%) responded to the patient questionnaire. The number of chronic dialysis patients in Japan continues to increase every year; as of the end of 2018, it had reached 339,841 patients, representing 2688 patients per million population. Among the prevalent dialysis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 4 publications
2
108
0
Order By: Relevance
“…Thanks to great advances in dialysis technologies, the circumstances of dialysis patients have been changing dramatically. For example, the proportion of facilities with ultrapure dialysate (endotoxin level in dialysate lower than 0.001 EU/mL) increased from 43.1% in 2009 to 74.6% in 2018 [ 3 ], and the number of patients treated with online hemodiafiltration increased dramatically from 16,853 (5.8% of all maintenance dialysis patients) in 2009 to 144,686 (42.0%) in 2019 in Japan [ 4 ]. All of these improvements may contribute to a better quality of life and a lower mortality rate in dialysis patients in the world, however, the Japanese registry data also show that the crude mortality rate in these patients has been almost the same, approximately 10%, in recent years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to great advances in dialysis technologies, the circumstances of dialysis patients have been changing dramatically. For example, the proportion of facilities with ultrapure dialysate (endotoxin level in dialysate lower than 0.001 EU/mL) increased from 43.1% in 2009 to 74.6% in 2018 [ 3 ], and the number of patients treated with online hemodiafiltration increased dramatically from 16,853 (5.8% of all maintenance dialysis patients) in 2009 to 144,686 (42.0%) in 2019 in Japan [ 4 ]. All of these improvements may contribute to a better quality of life and a lower mortality rate in dialysis patients in the world, however, the Japanese registry data also show that the crude mortality rate in these patients has been almost the same, approximately 10%, in recent years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this phenomenon may vary, but an increase in the elderly population and changes in social behaviors are considered important factors associated with an increase in dialysis patients with lower physical activity and frailty, resulting in lower quality of life and higher mortality. In fact, the proportion of dialysis patients who have been on dialysis for more than 20 years increased from less than 1% in 1992 to 8.4% at the end of 2018 [ 3 , 5 ]. As a result, the percentage of patients with multiple disabilities has also increased.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease, including heart failure, is a major complication induced by excess sodium with fluid retention; its prevalence and severity also increase from early stage CKD to end-stage renal disease [ 1 ]. Indeed, heart failure was the most common cause of death (23.5%) in all-cause deaths in dialysis patients [ 2 ]. Therefore, in the field of HD therapy, it is important to adequately manage patients’ body fluid status to prevent the prevalence of heart failure [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence has been affected by multiple factors, including body fluid excess, hypertension, anemia, and mineral bone disorder [ 1 ]. In addition, heart failure was reportedly the most important cause of death in patients on HD [ 2 ]. Therefore, adequate body fluid management is necessary to prevent the onset of cardiovascular disease, including congestive heart failure (CHF), and to improve patient prognosis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multivariable results showed that older age and DN were significantly associated with stroke and/or death, which may be due to the effects of increased mortality in the late period when the population was older. DN remains the leading cause of dialysis initiation in both Japan and the United States, but the increasing trend has slowed down [ 15 , 16 , 17 ]. Previous studies have reported that early detection and effective intervention of DM, as well as improved chronic kidney disease management in patients with DM, may contribute to preventing the transition to severe DM and DN and reducing stroke [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%